2023
DOI: 10.1177/03010066231200693
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wearing an opaque or transparent face mask on the perception of facial expressions: A comparative study between Japanese school-aged children and adults

Yuki Miyazaki,
Miki Kamatani,
Shuma Tsurumi
et al.

Abstract: The negative side effects of mask-wearing on reading facial emotional cues have been investigated in several studies with adults post-2020. However, little is known about children. This study aimed to determine the negative influence of mask-wearing on reading emotions of adult faces by Japanese school-aged children, compared to Japanese adults. We also examined whether this negative influence could be alleviated by using a transparent face mask instead of an opaque one (surgical mask). The performance on read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…The literature has been variable, with some studies implying a significant impact on children and others implying a negligible effect. 27,28,30,34,37,39,50,53,55,56,60,64 Interestingly, while Ruba et al 53 found that children were slightly more accurate in inferring emotions when faces were uncovered, compared with when reviewing pictures of faces with masks, there was no difference in their accuracy between faces with sunglasses and masks. Therefore, it is essential to understand the impact of these effects, rather than solely establishing an effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has been variable, with some studies implying a significant impact on children and others implying a negligible effect. 27,28,30,34,37,39,50,53,55,56,60,64 Interestingly, while Ruba et al 53 found that children were slightly more accurate in inferring emotions when faces were uncovered, compared with when reviewing pictures of faces with masks, there was no difference in their accuracy between faces with sunglasses and masks. Therefore, it is essential to understand the impact of these effects, rather than solely establishing an effect.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach could be used in establishing the effects of masks on children's ability to read others‘ facial expressions and process speech. The literature has been variable, with some studies implying a significant impact on children and others implying a negligible effect 27,28,30,34,37,39,50,53,55,56,60,64 . Interestingly, while Ruba et al 53 found that children were slightly more accurate in inferring emotions when faces were uncovered, compared with when reviewing pictures of faces with masks, there was no difference in their accuracy between faces with sunglasses and masks.…”
Section: Discussionmentioning
confidence: 99%
“…We employed jsPsych (de Leeuw, 2015) and Cognition (https://www.cognition.run/) for stimulus control and data collection. In line with previous studies addressing surgical masks (e.g., Carragher & Hancock, 2020;Dudarev et al, 2022;Grundmann et al, 2021;Kamatani et al, 2021Kamatani et al, , 2023Miyazaki et al, 2022Miyazaki et al, , 2023Miyazaki & Kawahara, 2016;Noyes et al, 2021), we used photographic images as stimuli. Ten AI-generated human faces (five males and five females) were selected from https://www.photo-ac.com/main/genface.…”
Section: Methodsmentioning
confidence: 99%